A Photochemical Two-Step Formal [5+2] Cycloaddition: A Condensation–Ring-Expansion Approach to Substituted Azepanes - Thullen, Scott M.; Rubush, David M.; Rovis, Tomislav (Synlett, 2017)
Seven-membered nitrogen-containing heterocycles are considerably underrepresented in the literature compared to their five- and six-membered analogues. Herein, we report a relatively understudied photochemical rearrangement of N-vinylpyrrolidinones to azepin-4-ones in good yields. This transformation allows for the conversion of readily available pyrrolidinones and aldehydes to densely functionalized azepane derivatives in a facile two-step procedure.
Keywords: azepane; photochemistry; photo-Fries rearrangement; heterocycles; [5+2] cycloaddition